Pengaruh Dukungan Sosial Teman Sebaya dan Stres Akademik Terhadap Resiliensi Akademik Mahasiswa Tingkat Akhir yang Sedang Mengerjakan Skripsi - Dinny Rida Bastari; Vira Sandayanti; Prida Harkina (Program Studi Psikologi Islam, 2026)
This study aims to analyze the influence of peer social support and academic stress on the academic resilience of final year students working on their thesis. Academic resilience is a student's ability to withstand and recover from pressure and challenges that arise during the thesis writing process. This study uses a quantitative approach with a survey method involving 271 students from six universities in Bandar Lampung City. The data collection instrument is a closed questionnaire using a Likert scale to measure three variables: peer social support, academic stress, and academic resilience. Data analysis was carried out using multiple linear regression tests, as well as classical assumption tests such as normality, multicollinearity, and heteroscedasticity tests. The results show that peer social support has a positive and significant effect on the academic resilience of final year students. Meanwhile, academic stress and academic resilience have no significant effect. The peer social support variable provides a greater contribution than academic stress, with coefficient values ​​of 0.730 and -0.017, respectively. The R-square value of 0.523 indicates that 52.3% of the variation in academic resilience can be explained by the two independent variables. This finding confirms the importance of both internal and external factors, indicating that academic resilience has a stronger relationship with peer social support than with academic stress. Thus, academic resilience makes a significant contribution in helping final-year students face academic challenges during the thesis writing process..